Mod mytologisk realisme i Nikodemusevangeliet - Nielsen, Jesper Tang (Dansk Teologisk Tidsskrift, 2016)
The Gospel of Nicodemus had its heyday in the Middle Ages. Today it attracts attention by only a few historians and practically no Biblical scholars. It is, however, a charming example of creative Biblical rewriting. The article provides an introduction to the text and its use of the New Testament gospels. It is possible to locate in it a number of typical narrative techniques and tendencies. This Gospel supplies the New Testament gospel narrative with new episodes and expands the known figures into new narratives. It aims to tell every detail from the New Testament in concrete narratives. In this way it moves in the direction of realism. At the same time it enhances the supernatural features of the narrative. In this way it moves in the direction of mythology. Thus, the Gospel of Nicodemus may tentatively be seen as a specimen of mythological realism.